Performance and vibration characteristics of 4-cycle 4-cylinder in-line engine equipped with second mode balancer system as compared to conventional engine - Khoonavuthi Damrongplasit (Chulalongkorn University, 2014)
Thesis (M.Eng.)--Chulalongkorn University, 1980